MIA’S PSYCHOPATHY IN MOULY SURYA’S FIKSI - Pricillia Chandra; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This study aims to discuss Mia’s psychopathic symptoms through the 18 items described in Psychopathy Checklist—Revised four-factor model. The purpose of this analysis is to discuss what psychopathic category Mia belongs to and to discuss why Mia, as a psychopathic person, commits suicide. The analysis shows that Mia’s psychopathic symptoms fit these factors, and through it, the score can be given to each item discussed in the analysis. Moreover, it also shows that one of the factors, which is the factor of lifestyle, affects the probability of a psychopath to commit suicide because of the impulsivity that a psychopath has. In the end, it can be concluded that Mia is a psychopathic person who can be categorized as an intermediate psychopath, and her suicidal act is affected by her past traumatic experience and her impulsivity.